Association between pulmonary hemorrhage and CPAP failure in very preterm infants - Wang, Li; Zhao, Li-li; Xu, Jia-ju; Yu, Yong-hui; Li, Zhong-liang; Zhang, Feng-juan; Wen, Hui-min; Wu, Hai-huan; Deng, Li-ping; Yang, Hui-yu; Li, Li; Ding, Lan-lan; et al. (Frontiers in Pediatrics, 2022)
Background Pulmonary haemorrhage (PH) in neonates is a life-threatening respiratory complication. We aimed to analyze the perinatal risk factors and morbidity with PH among very preterm infants in a large multicentre study. Methods This was a multicentre case–control study based on a prospective cohort. Participants included 3680 in-born infants with a gestational age at 24 to 32 weeks (birth weight <1500 g) who were admitted between January 1, 2019, and October 31, 2021. All infants were divided into two groups, namely, the PH and no-PH groups, at a ratio of 1:2 according to the following factors: gestational age (GA), birth weight (BW), and the Score for Neonatal Acute Physiology with Perinatal extension II (SNAPPE II). Perinatal factors and outcomes were compared between the two groups by logistic regression analyses. Results A total of 3680 infants were included in the study, and the number of identified cases of PH was 262 (7.1%). The incidence was 16.9% (136/806) for neonates with extremely low BW (BW < 1000 g) infants. The multivariate analysis showed that CPAP failure (OR 2.83, 95% CI 1.57, 5.08) was significantly associated with PH. PH was associated with a high likelihood of death (OR 3.81, 95% CI 2.67, 5.43) and bronchopulmonary dysplasia (BPD) (≥ grade II) (OR 1.58, 95% CI 1.00, 2.48). Conclusions In this multicentre case–control study based on a prospective cohort, PH to be common among VLBW infants. PH is associated with significant morbidity and mortality, and perinatal management, especially CPAP failure. Respiratory management strategies to decrease the risk of PH should be optimized.